THE USE OF STATE PROTECTIVE DUTIES BY THE INTER-AMERICAN SYSTEM FOR THE PROTECTION OF HUMAN RIGHTS: ANALYSIS BY THE LIGHT OF SLAVERY IN BRAZIL - Azevedo, Douglas Matheus de; Hennig Leal, Mônia Clarissa (Unoesc International Legal Seminar, 2017)
Having as a background the persistence of moderns forms of slavery in Brazil, direct result of it’s historical heritage which culminated in the denunciation by the Inter-american Comission on Human Rights of the country to the Inter-american Court of Human Rights, possibly resulting in a new condemnation, this research seeks to identify the fundaments used by the Inter-american System for the Protecton of Human Rights on it’s reports, recomendations and decisions, more precisely if notions of state protective duty are used. Thus, in a first moment the focus of this research will be in a brief exposure of the social context that the regions in which forced labor and slavery were more intense, the modus operandi used to recruit workers from poor regions and general notions regarding the Inter-American System, since it was created to correct structural deficiencies of these member-countries. After that, the Fazenda Brazil Verde case will be analysed – the one that originated the denunciation -, to verify the fundaments used in the positive measures recomended by the Comission and that most likelly are going to be used by the Inter-American Court in case of condemnation. The conclusion is that the Inter-American System uses notion of state protective duties in it’s recomendations and decisions, even though not in its express form, seeking more than just make individual amends to the victims, but to correct insuficiencies of the State, thus preventing new violations.